2014
DOI: 10.1517/14656566.2014.972367
|View full text |Cite
|
Sign up to set email alerts
|

Triple combinations in chronic obstructive pulmonary disease – is three better than two?

Abstract: A growing body of evidence suggests that triple therapy with an antimuscarinic agent, a long-acting β2-agonist, and an inhaled corticosteroid is efficacious in patients with more severe chronic obstructive pulmonary disease (COPD), such as those with frequent exacerbations. Moreover, this therapy is often prescribed in real-life management of COPD, even in patients who are not suffering from severe COPD. All this makes triple therapy an attractive therapeutic approach. Therefore, a variety of triple combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Meta-analyses and real-life retrospective analyses seem to support the use of triple therapy using multiple inhalers in patients with COPD [17]. Recently, several meta-analyses have attempted to clarify the role of triple therapy delivered from a single inhaler in COPD also because they have been able to include the results of the RCTs with triple therapy that have gradually been released to the scientific community.…”
Section: Meta-analyses Evaluating Triple Therapy In Copdmentioning
confidence: 99%
“…Meta-analyses and real-life retrospective analyses seem to support the use of triple therapy using multiple inhalers in patients with COPD [17]. Recently, several meta-analyses have attempted to clarify the role of triple therapy delivered from a single inhaler in COPD also because they have been able to include the results of the RCTs with triple therapy that have gradually been released to the scientific community.…”
Section: Meta-analyses Evaluating Triple Therapy In Copdmentioning
confidence: 99%
“…COPD is mainly treated with drugs, such as bronchodilators and corticosteroids. In addition, the use of antioxidants and vitamin D is currently being investigated clinically, but the results have not been satisfactory to date 13,14. Recent basic and clinical studies have revealed that hydrogen is an important physiologic regulatory molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Поэтому в настоя-щее время разрабатываются различные тройные комбинации [44]. Однако только вилантерол/умекли-диний/флутиказона фуроат является единственной разрабатываемой тройной комбинацией, которая включает в себя ультра-ДДБА.…”
Section: обзорыunclassified